Philosophy-Based Learning as The Foundation for Developing Critical Thinking Skills In Elementary Schools - Islami, Raya Amanda Nur; Herlambang, Yusuf Tri (International Conference on Elementary Education, 2025)
Philosophy is often viewed as a subject for adults, yet the acts of thinking and questioning are natural instincts in children. In primary education, philosophy especially through the Philosophy for Children approach has great potential to build critical, reflective, and ethical thinking from an early age. This study explores the application of philosophy in elementary education and its relevance to character development and critical thinking skills. A qualitative literature review method was used by examining various national and international studies on philosophy for children. Thematic analysis was applied to identify patterns, main concepts, and practical implications of philosophy in schools. The findings show that philosophy-based learning through dialogic discussion and the Socratic method improves students’ critical thinking, empathy, communication, and moral awareness. Teachers serve as philosophical facilitators who guide students to ask questions, reason, and reflect logically. However, implementing philosophy for children still faces challenges such as limited teacher training, lack of time, and the need for cultural adaptation of topics. In conclusion, philosophy education in primary schools develops not only intellectual capacity but also moral wisdom and reflective character. Thus, integrating philosophy for children into curricula and teacher training is a strategic step toward humanistic and context-based education.